Associations between the Strengths and Difficulties Questionnaire (SDQ) and Tests of Variables of Attention (TOVA) in rural school-aged children in Benin Africa - Roméo Zoumenou; Nathalie Costet; Michael J. Boivin; Jaqueline Wendland; Florence Bodeau-Livinec (Cambridge Prisms: Global Mental Health)
Sub-Sahara Africa (SSA) children are at high-risk neurodevelopmentally due to the prevalence of infectious disease, nutritional deficiencies and compromised caregiving. However, few mental health screening measures are readily available for general use. The Strengths and Difficulties Questionnaire (SDQ) has been used as a mental health screening measure in the SSA, but its psychometric properties are not well understood. Five hundred and sixty-six mothers completed the SDQ for their 6-year-old children in rural Benin north of Cotonou. These were mothers who had been part of a malarial and intestinal parasite treatment program and micronutrient fortification intervention program during pregnancy for these children. Their study children (N = 519) completed the computerized Tests of Variables of Attention (TOVA-visual) as a performance-based screening assessment of attention deficit and hyperactivity disorders. In evaluating the relationship between the SDQ and TOVA, we controlled for maternal risk factors such as depression, poor socioeconomic status and educational level, along with the child’s schooling status. TOVA measures of impulsivity were significantly related to SDQ emotional and hyperactivity/inattention difficulties. TOVA inattention was related to SDQ emotional difficulties. The triangulation of maternal risk factors (e.g., depression), the SDQ and the TOVA can provide effective screening for mental health issues in SSA children.